Clinical predictors of incipient vertebral fractures and bone mineral density in kidney transplant patients - APAYDIN, TUĞÇE; VELİOĞLU, ARZU; YAVUZ, DİLEK; BUĞDAYCI, ONUR; TUĞLULAR, ZÜBEYDE SERHAN (My University, 2022)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.Purpose: Kidney transplant recipients are prone to metabolic bone diseases and consequent fractures. This study aimed to evaluate the incidence of incipient vertebral fractures, osteopenia, osteoporosis, and the clinical factors associated with incipient vertebral fractures in a group of kidney transplant patients. Methods: Two hundred sixty-four patients (F/M 124/140, 45.3 ± 13 years) who had undergone kidney transplantation in tertiary care centers were included. Vertebral fractures were assessed semiquantitatively using conventional thoracolumbar lateral radiography in 202 of the patients. Results: Vertebral fractures were observed in 56.4% (n = 114) of the study group. The frequency of osteoporosis was 20.0% (53 of 264 patients), and osteopenia was 35.6% (94 of 264 patients). Bone mineral density (BMD) levels were in the normal range in 40.3% (n = 46) of the subjects with vertebral fractures. It was in the osteoporotic range in 20.1% (n = 23) and the osteopenic range in 40.3% (n = 46). Vertebral fractures were associated with age, duration of hemodialysis, BMI, and femoral neck Z score (R2 37.8%, p = 0.027). Conclusion: As incipient vertebral fractures can be observed in patients with normal BMD levels in kidney transplant recipients, conventional X-ray screening for vertebral fractures may be beneficial for a proper therapy decision of metabolic bone disease in kidney transplant recipients.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Orthopedics and Traumatology; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); ORTOPEDİ; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); ORTHOPEDICS; Neurology (clinical); Orthopedics and Sports Medicine; Podiatry; Life Sciences; Bone loss; Renal transplantation; Spinal fractures; Osteopenia; Osteoporosis; X-RAY ABSORPTIOMETRY; RENAL-TRANSPLANTATION; POSTMENOPAUSAL WOMEN; RISK-FACTORS; PREVALENCE; OSTEOPOROSIS; HYPERPARATHYROIDISM; OSTEOPENIA; RECIPIENTS; DISEASE